2020
DOI: 10.3390/ijerph17155334
|View full text |Cite
|
Sign up to set email alerts
|

How to Evaluate Provincial Ecological Civilization Construction? The Case of Jiangsu Province, China

Abstract: Ecological civilization is a transcendence of industrial civilization. The improvement of China’s ecological civilization system can not only provide developing countries with an empirical reference for ecological civilization construction, but also make a huge contribution to the progress of global ecological civilization. This paper focuses on improving the provincial ecological civilization evaluation system. First, the Provincial Ecological Civilization Construction Evaluation Index System is established a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…In the field of economic development, policy objectives have shown significant effectiveness, but policy power, policy feedback, and policy measures have not reached a significant level. Economic development targets have been receiving more attention as the focus of local government performance reviews [ 62 , 63 ]. For example, Du et al [ 63 ] argue that the key to coordinated development is to achieve a win–win situation between economic development and ecological protection.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of economic development, policy objectives have shown significant effectiveness, but policy power, policy feedback, and policy measures have not reached a significant level. Economic development targets have been receiving more attention as the focus of local government performance reviews [ 62 , 63 ]. For example, Du et al [ 63 ] argue that the key to coordinated development is to achieve a win–win situation between economic development and ecological protection.…”
Section: Discussionmentioning
confidence: 99%
“…The index systems are diverse because of the wide range of research themes and scales. Second, relevant studies focus on the urban [26,29] and sub-national scales [30]. In recent years, research on BRI countries has become more common.…”
Section: Assessment Of Green Development Capabilitymentioning
confidence: 99%
“…Third, from the perspective of ecological civilization research, most scholars have studied the development of ecological civilization at the provincial, municipal, and rural levels [ 10 , 11 , 12 , 13 ]. Fourth, the results of existing studies have shown that the quality of economic development and nature conservation [ 14 , 15 , 16 ], clean energy investment, water supply for urban residents, foreign investment utilization, land resource protection, and population education quality [ 17 ] have significant effects on the level of ecological civilization construction. The results of these studies have shown that the industrial structure and marketization degree, government environmental risk awareness, government green action, residents’ happiness, corporate environmental responsibility, investment in culture and education, green travel and ecological construction, and other factors positively affect the performance of ecological civilization [ 7 ].…”
Section: Introductionmentioning
confidence: 99%